2012
DOI: 10.1091/mbc.e12-02-0132
|View full text |Cite
|
Sign up to set email alerts
|

Collagen/β1 integrin signaling up-regulates the ABCC1/MRP-1 transporter in an ERK/MAPK-dependent manner

Abstract: The mechanisms by which β1 integrins regulate chemoresistance of cancer cells are still poorly understood. In this study, we report that collagen/β1 integrin signaling inhibits doxorubicin-induced apoptosis of Jurkat and HSB2 leukemic T-cells by up-regulating the expression and function of the ATP-binding cassette C 1 (ABCC1) transporter, also known as multidrug resistance–associated protein 1. We find that collagen but not fibronectin reduces intracellular doxorubicin content and up-regulates the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 59 publications
2
44
0
Order By: Relevance
“…A well-known cellular physiological adaptation contributing to chemoresistance in leukemia is enhanced expression and activity of drug efflux transporters (36). A recent CAM-DR study reported that integrin-␤1 mediated adhesion of Jurkat cells stimulated the expression of the p-glycoprotein transporter MRP1 and decreased intracellular accumulation of doxorubicin (37).…”
Section: Resultsmentioning
confidence: 99%
“…A well-known cellular physiological adaptation contributing to chemoresistance in leukemia is enhanced expression and activity of drug efflux transporters (36). A recent CAM-DR study reported that integrin-␤1 mediated adhesion of Jurkat cells stimulated the expression of the p-glycoprotein transporter MRP1 and decreased intracellular accumulation of doxorubicin (37).…”
Section: Resultsmentioning
confidence: 99%
“…The upregulation of genes promoting cell cycle arrest might be explained by mechanisms of derepression invoked as a result of the ablation of β1 integrin, whereas the upregulation of genes supporting cell cycle progression might reflect an attempt to overcome the proliferative defect caused by the loss of β1 integrin signaling. Accordingly, loss of β1 integrin signaling is supported by the observed downregulation of some of the cyclins or cyclin kinases, as well as of MAPK activity, which are known downstream effectors of β1 integrin signaling (Chiang et al, 2011;D'Amico et al, 2000;El Azreq et al, 2012;Saleem et al, 2009;Velling et al, 2004). Also of interest is the downregulation of Ovol2 and Tuba1.…”
Section: Research Article Integrins In Islet Developmentmentioning
confidence: 99%
“…We did not elucidate the exact mechanism for integrin β 1 -mediated chemoresistance in ELA cells; however, it has been shown that integrin β 1 silencing sensitizes non-small cell lung cancer cells to cisplatin treatment due to a defective activation of the EGFR signaling cascade [94]. Another mechanism mediating cisplatin resistance in ELA cells could involve integrin β 1 -mediated up-regulation of the multidrug resistance-associated protein-1 (MRP-1), as binding of collagen to integrin β 1 has been found to up-regulate expression and activity of MRP-1 in leukemic T-cells [95], and expression of MRP-1 has been correlated to cisplatin resistance of lung cancer cells [96]. Knockdown of integrin β 1 did not affect the sensitivity of ELA cells to gemcitabine, pointing to other resistance mechanisms for this drug.…”
Section: Discussionmentioning
confidence: 99%